Advanced Weather Intelligence Helps Utilities Prepare for Severe Weather. Issue 3 (1st March 2015) - Spence, Shannon; Foerster, Jim
Abstract : Water utility operators have long known that the weather can have the single biggest impact on their operations. The increasing intensity and frequency of rainfall patterns, along with increasingly violent storms, is creating new challenges for water utility operators across the country. In 2007, the Intergovernmental Panel on Climate Change ‐ a panel that assesses the scientific, technical, and socioeconomic information relevant for the understanding of the risk of human‐induced climate change ‐ concluded that intense rain events have become more frequent in the past 50 years. This, combined with increased runoff from land use changes, means more significant flash‐flood events could occur.